PENGARUH GREEN ACCOUNTING, MEDIA EXPOSURE DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Sinta Aprilia; Lilis Lasmini; Meliana Puspitasari (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study aims to analyze the effect of Green Accounting, Media Exposure, and Leverage on Tax Aggressiveness in Healthcare sector companies for the period 2019-2023. The research method used is quantitative with analysis techniques (PLS-SEM) using SmartPLS. This study uses secondary data sourced from the financial statements of companies listed on the Indonesia Stock Exchange (IDX). The results of the study indicate that Leverage has a positive and significant effect on Tax Aggressiveness, which means that the higher the leverage of a company, the more aggressive its tax strategy. Meanwhile, Green Accounting has a negative relationship with Tax Aggressiveness, but the effect is not significant, so it cannot be concluded that the implementation of Green Accounting actually suppresses tax aggressiveness. Media Exposure also does not show a significant effect on Tax Aggressiveness, which indicates that media attention does not necessarily affect the company's tax policy. The conclusion of this study is that leverage is the main factor in determining the company's tax aggressiveness, while Green Accounting and Media Exposure have not been proven to have a significant effect. Therefore, further research can explore other factors that have the potential to influence tax aggressiveness more comprehensively.